On α-Layer Ideal Topologies - Xiu-Yun Wu; Li-Li Xie (Advances in Fuzzy Systems)
The purpose of this paper is to study theory of two different kinds of α-layer order-preserving operator space, namely, ωα-opos and ωα*(ℑ)-opos. The former kind of space is formed by α-layer function in L-fuzzy order-preserving operator space. The later kind of space is derived by local α-remote neighborhood function, which is related with ωα-opos and α-ideal. We study characteristic properties of the two kinds of spaces, respectively, and give some applications to show the intimate relations under two different ωα*(ℑ)-oposs.